Discriminant validity, responsiveness and reliability of the rheumatoid arthritis-specific Work Productivity Survey (WPS-RA) - Osterhaus, Jane T; Purcaru, Oana; Richard, Lance (Arthritis research & therapy, 2009)
The rheumatoid arthritis-specific Work Productivity Survey (WPS-RA) measures the impact of rheumatoid arthritis (RA) and treatment on patient productivity within and outside the home. It contains nine questions addressing employment status, productivity within and outside the home, and daily activities. The objective of this paper was to evaluate the discriminant validity, responsiveness, and reliability of the WPS-RA in patients with active RA. Two hundred twenty subjects (mean age was 53.8 years, 83.6% were female, mean disease duration was 9.54 years, mean number of disease-modifying anti-rheumatic drugs failed was 2, and 38.6% were employed outside the home) in a phase III, 24-week, double-blind, placebo-controlled trial completed the WPS-RA at baseline and every 4 weeks until withdrawal/study completion. Validity was evaluated via known groups using baseline data (first and third quartiles of subjects' Health Assessment Questionnaire--Disability Index [HAQ-DI] scores and Short Form-36 health survey [SF-36] scores). To evaluate responsiveness, mean changes in WPS-RA at week 24 were compared between American College of Rheumatology 20% improvement criteria (ACR20) (or HAQ-DI) responders and non-responders. Standardized response mean (SRM) was also used to quantify responsiveness. All group comparisons were conducted using a non-parametric bootstrap-t method. Subjects with lower HAQ-DI or SF-36 scores generally had statistically greater RA-associated losses in productivity within and outside the home compared with subjects with higher scores (25 of 32 evaluations were statistically significant). Smallest differences between groupswere seen in work absenteeism and days with outside help. At week 24, ACR20 and HAQ-DI responders reported large improvements in productivity within and outside the home; non-responders reported mainly a worsening in productivity (P <or= 0.05). Effect size for productivity changes in ACR20 or HAQ-DI responders was moderate to large for six out of eight items (SRM = 0.48 to 1.12). The effect size was small for work absenteeism and days with outside help. (SRM = 0.4 and 0.24, respectively). In non-responders, the magnitude of change was negligible (SRM < 0.1) or small (SRM < 0.3). The WPS-RA has demonstrated properties of discriminative validity, reliability, and responsiveness for the measurement of productivity within and outside the home in subjects with active RA.